Pelatihan Trekking Berbasis Tri Mandala Sebagai Upaya Menurunkan Stres Dan Meningkatkan Kebugaran Lansia - Ni Putu Sri Arnita; Ni Luh Putu Mia Lestari Devi; Dhea Anisa Fitriani (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2023)
The covid-19 outbreak has an impact on all aspects of the lives of the elderly, including their psychosocial conditions. These psychosocial problems have an impact on increasing stress and decreasing fitness. The specific aim of research is to know and implement trekking based Tri Mandala decrease stress and increase fitness of elderly. The specific aim of research is to know and implement trekking based Tri Mandala decrease stress and increase fitness of elderly. Through a quasi experimental with the same subject design (treatment by subject design) and randomized posttest only group design assessed trekking based Tri Mandala training to reducing stress was recorded by Stress Questionnaire and improve fitness was recorded by rockspot method. The data obtained were analyzed by paired t-test at a significance level of 5%. The result showed that, trekking based Tri Mandala training reducing stress of eldery to 13,54% and increase fitness of eldery to 42,08%. It concluded that trekking based Tri Mandala training reduce stress and improve the fitness of elderly.